Review of vaccine effectiveness assumptions used in economic evaluations of infant pneumococcal conjugate vaccine. (2nd January 2018) - Wasserman, Matt; Sings, Heather L; Jones, Dylan; Pugh, Sarah; Moffatt, Margaret; Farkouh, Raymond
ABSTRACT: Introduction : Pneumococcal conjugate vaccines (PCVs) have provided a significant clinical and economic impact globally. The majority of countries which have implemented an infant PCV program have observed a substantial reduction in the burden of invasive pneumococcal disease (IPD), pneumococcal pneumonia, and acute otitis media (AOM) due to vaccine serotypes. After 17 years of use, many countries have evaluated and re-evaluated the value of their vaccine program using cost-effectiveness analyses; however, many of these analyses do not reflect the current body of evidence. Areas covered : This literature review summarizes key assumptions used in cost-effectiveness analyses for PCVs and discusses whether these should be refined. Expert commentary : Many existing models continue to project cost-effectiveness of implementing a PCV program into a naïve population, despite sustained PCV use. Furthermore, many assumptions related to program effectiveness are based on evidence from controlled studies or extrapolated from vaccines that are no longer or were never used. Real world effectiveness data published from nearly 10 years of higher-valet vaccine use should be reflected in key assumptions that drive decision makers to choose one vaccine over another. As data continuously emerges, cost-effectiveness of programs should be evaluated in the context of the most current data.